PENGEMBANGAN MEDIA PEMBELAJARAN MATA PELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DENGAN APLIKASI POWTOON DI MA MUHAMMADIYAH TALU - Tuti Yuniza; Sarwo Derta; Supratman Zakir; Riri Okra (Lembaga Pengembangan Kinerja Dosen, 2023)
Every innovation is created to provide positive benefits for human life. Providing many conveniences, as well as a new way of carrying out human activities, especially in the field of information technology, has enjoyed many benefits brought about by the innovations that have been produced in the last decade. As time goes by, education is also growing. The development of science and technology encourages renewal efforts in the use of technological results in the teaching and learning process. Learning media can be regarded as learning aids, namely anything that can be used to stimulate thoughts, feelings, attention and abilities or skills of students so that they can encourage the learning process. This limitation is still quite broad and deep, including the understanding of sources, environment, people and methods used for learning purposes. Information and communication technology learning media is made using powtoons and an added application, namely linktree. The type of research used is a type of research and development (Research and Development). The R&D model used is the 4-D (four D) version, namely Define, Design, Develop, and Disseminate, using the Luther-Sutopo multimedia development model, which consists of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. Based on the results of the research that has been done, it can be concluded that the resulting application can be utilized and is suitable for use by students and teachers in the subject concerned. The results of the validity test by experts on Android-based learning media obtained an average value of 0.94, namely valid, the practicality test obtained an average value of 4.39 in the very high category, and the effectiveness test obtained an average value of 0.72 in the very category. effective.